Twisted bimodules and Hochschild cohomology for self-injective algebras of class A(n), II - Erdmann, K; Holm, T; Snashall, N (2002)
Up to derived equivalence, the representation-finite self-injective algebras of class An are divided into the wreath-like algebras (containing all Brauer tree algebras) and the Möbius algebras. In Part I (Forum Math. 11 (1999), 177-201), the ring structure of Hochschild cohomology of wreathlike algebras was determined, the key observation being that kernels in a minimal bimodule resolution of the algebras are twisted bimodules. In this paper we prove that also for Möbius algebras certain kernels in a minimal bimodule resolution carry the structure of a twisted bimodule. As an application we obtain detailed information on subrings of the Hochschild cohomology rings of Möbius algebras.